A Qualitative Analysis of Obstacles and Obstacles in Implementing the EDLINK Application at the Surakarta - Lailla Hidayatul Amin; Muhammad Ja'far Nashir; Haidar Abdullah; Nurul Aulia; Ahmad Najmuddin Zaki (Universitas Muhammadiyah Enrekang, 2024)
This research aims to conduct a qualitative analysis of the obstacles and obstacles that arise in implementing the EDLINK application at the Mamba’ul ‘Ulum Islamic Institute, Surakarta. This research uses a qualitative method with a case study approach. Data was collected through in-depth interviews with key informants, namely lecturers, administrative staff and students involved in using the EDLINK application. Other techniques used are observation and document analysis. Data were analyzed using qualitative data analysis techniques. The collected data was analyzed through a categorization process to identify the obstacles and barriers experienced by lecturers and students in using the EDLINK application. Based on the research results, it can be concluded that there are several obstacles and obstacles in implementing the EDLINK application at the Mamba’ul ‘Ulum Islamic Institute, Surakarta. Factors that cause these obstacles include limited infrastructure, lack of training and socialization, changes in work culture, and resistance factors. It is hoped that the results of this research will provide a comprehensive picture of the challenges faced in integrating technology in the higher education academic system. The findings of this research can provide valuable insight for the Mamba’ul ‘Ulum Islamic Institute to increase the effectiveness of implementing the EDLINK application and overcome obstacles that arise in the process. In addition, it is hoped that this research can contribute to the literature regarding the integration of technology in higher education academic systems.